1984
DOI: 10.1128/jcm.19.3.305-310.1984
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fatty acids of the genus Rochalimaea by electron capture gas chromatography: detection of nonanoic acid

Abstract: The fatty acid compositions of Rochalimaea quintana, strains Fuller and Guadalupe, and R. vinsonii, the Canadian vole agent, were determined in an effort to further characterize these bacteria. The cells were saponified with 5% NaOH in 50% methanol and acidified to pH 2. The methanolysates were extracted with chloroform, derivatized with 2,2,2-trichloroethanol, and analyzed using a Hewlett-Packard gas chromatograph equipped with a frequency pulse-modulated electron capture detector and a 3% OV-101 packed-glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…CFAs of Rochalimaea quintana grown on blood agar medium resemble the other rickettsial CFAs except that they lack the 3-OH-C14:0 found in the others. Additional studies have examined Rochalimaea quintana and revealed similar findings (135,162). That C18l: accounts for such a large percentage of the total CFAs (40 to 60%) is a distinctive feature of Rochalimaea quintana.…”
Section: Characterization Of Othermentioning
confidence: 66%
See 1 more Smart Citation
“…CFAs of Rochalimaea quintana grown on blood agar medium resemble the other rickettsial CFAs except that they lack the 3-OH-C14:0 found in the others. Additional studies have examined Rochalimaea quintana and revealed similar findings (135,162). That C18l: accounts for such a large percentage of the total CFAs (40 to 60%) is a distinctive feature of Rochalimaea quintana.…”
Section: Characterization Of Othermentioning
confidence: 66%
“…That C18l: accounts for such a large percentage of the total CFAs (40 to 60%) is a distinctive feature of Rochalimaea quintana. In contrast to other researchers, Westfall et al (162) analyzed Rochalimaea quintana and related species by electron capture GLC and reported that it contained C9:0. However, they noted that complex media may have been the source of this unusual CFA.…”
Section: Characterization Of Othermentioning
confidence: 84%
“…Red beans are cultivated and harvested mechanically. To facilitate mechanical harvesting, the stems and leaves of red bean plants should be fully dried [18,22]. The use of natural methods may cause inconsistent drying between different parts of the whole plant due to climatic factors like rainfall, and even red bean yield reduction resulted from moldy beans.…”
Section: Introductionmentioning
confidence: 99%
“…In the detection of nonanoic acid, due to the high polarity and low volatility of fatty acids with a high carbon number, precolumn derivatization combined with gas chromatography-electron capture detection (GC-ECD) has been employed for nonanoic acid detection [6,7,22] to improve the analytical sensitivity. Qualitative and quantitative analysis of fatty acids can also be performed by means of GC without derivatization [10,13,14,17,21], especially for the analysis of lowunsaturation and short-chain fatty acids.…”
Section: Introductionmentioning
confidence: 99%